Spatial Correlation Function of Signals in Radio Engineering Systems with Phased Antenna Arrays - M. R. Bibarsov (Известия высших учебных заведений России: Радиоэлектроника, 2025)
Aim. To determine the dimensions of the high correlation region by studying the shape of a volumetric image of the module of the spatial correlation function, depending on the direction of arrival of the signal of interest.Materials and methods. The uncertainty function of the space–time signal was investigated using statistical simulation methods. Calculations were performed in the Mathcad 15 software package.Results. A volumetric image of the ambiguity function module of a space–time signal is constructed. The minimum and maximum values of the width of the high correlation region are determined by angular coordinates, which directly affect the accuracy of direction finding of the repeater satellite using a graphical method. At an elevation angle equal to zero, the minimum value of the width of the correlation function is obtained, equal to θкор = θкор min = 7° and the maximum uncertainty in relation to the true value of the azimuth. At the boundary of the scanning area of the radiation pattern θ0 = 60°, we obtain θкор max = 12°, in this case, the parameter Aкор min = 7°. The analytical method allowed us to obtain: Aкор min » 6° at θ0 = 60°; A0 = 90, 270° and θкор min » 5° at θ0 = 0°; A0 = 0,180, 360°.Conclusion. The results obtained can be used when developing mobile space communication systems with phased antenna arrays. Further research directions include the development of conformal phased antenna arrays with a controllable directional diagram.